2015
DOI: 10.1371/journal.pone.0131735
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Prostaglandin Transporter PGT Lowers Blood Pressure in Hypertensive Rats and Mice

Abstract: Inhibiting the synthesis of endogenous prostaglandins with nonsteroidal anti-inflammatory drugs exacerbates arterial hypertension. We hypothesized that the converse, i.e., raising the level of endogenous prostaglandins, might have anti-hypertensive effects. To accomplish this, we focused on inhibiting the prostaglandin transporter PGT (SLCO2A1), which is the obligatory first step in the inactivation of several common PGs. We first examined the role of PGT in controlling arterial blood pressure blood pressure u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
3
6
0
Order By: Relevance
“…As a functional correlate of these measurements, we also measured systolic and diastolic arterial blood pressure and heart rate in vehicle- and inhibitor-treated mice. As shown in Supplementary Figure 5, although the PGT inhibitor produced no change in blood pressure in these normotensive mice, a finding in accord with our previous report 37 , pharmacological PGT inhibition lowered resting heart rate significantly, an indicator of reduced sympathetic tone 38, 39 . In contrast to norepinephrine, urinary epinephrine, an index of systemic epinephrine release from the adrenal medulla 35 , was not affected, nor was the expression in iWAT of tyrosine hydroxylase, the rate limiting step in catecholamine synthesis (Supplementary Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…As a functional correlate of these measurements, we also measured systolic and diastolic arterial blood pressure and heart rate in vehicle- and inhibitor-treated mice. As shown in Supplementary Figure 5, although the PGT inhibitor produced no change in blood pressure in these normotensive mice, a finding in accord with our previous report 37 , pharmacological PGT inhibition lowered resting heart rate significantly, an indicator of reduced sympathetic tone 38, 39 . In contrast to norepinephrine, urinary epinephrine, an index of systemic epinephrine release from the adrenal medulla 35 , was not affected, nor was the expression in iWAT of tyrosine hydroxylase, the rate limiting step in catecholamine synthesis (Supplementary Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…7,23 Because T26A was demonstrated to possess 100 times lower activity to enzymes for PGE 2 synthesis, it has been used as a selective inhibitor for OATP2A1. 8,9 Although we did not examine whether suramin was a substrate for OATP2A1 and type of its inhibition, the present study demonstrates that suramin is the most potent inhibitor for OATP2A1 with IC 50,2A1 of 0.17 microM because its IC 50,MRP4 /IC 50,2A1 and IC 50,Syn /IC 50,2A1 were approximately 74 and 337, respectively (Figs. 3-5 and Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…FDA-approved drug library Japan version (CB-BML-2841J0100, Enzo Life Sciences Inc., Farmingdale, NY) was provided by Kanazawa University Cancer Research Institute. [5,6,8,11,12,14,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that inhibition of PGT would cause vasodilation. Indeed, in a separate study we found that T26A potentiated PGE 2 induced vasodilation of mouse aorta and reduced blood pressure in both mice and rats [ 43 ]. The vasodilatory effect of T26A could be a significant contributor to increased perfusion in hind limb.…”
Section: Discussionmentioning
confidence: 99%